A rare case of complicated pure posterior sternoclavicular dislocation in a young athlete: Sternoclavicular dislocation in adolescent - Calderazzi, Filippo; Menozzi, Margherita; Valenti, Piergiulio; Colacicco, Alessandra; Bastia, Paolo; Pogliacomi, Francesco; Ceccarelli, Francesco (Acta Biomedica Atenei Parmensis, 2020)
Sternoclavicular joint dislocation (SCJD) is a rare injury, generally classified in anterior and posterior. The posterior SCJD is very infrequent yet potentially associated with life-threatening complications. In patients with unfused medial clavicle physis, SCJD can be associated with fracture-dislocation (Salter type I or II).We hereby present the case of a 12- year-old basketball player with severe pain in sternoclavicular region and arising dysphagia after a fall and tackle by another player. A SCJ injury was hypothesised and the CT scan detected the presence of a true posterior SCJD with no associated fracture, which was also confirmed during open reduction. As the patient complained dysphagia, it was also necessary to study other possible mediastinal compressions by a contrast medium CT scan of the great vessels.The CT scanned brachiocephalic vein compression without additional clinical evidence or signs. Twenty hours after the trauma the patient underwent an unsuccessful closed reduction; for this reason, surgical treatment with open reduction and fixation was mandatory. After 12 weeks of therapy she returned to her previous sport activity.